The cost of business cycles for unskilled workers - Toshihiko Mukoyama; Aysegül Sahin (Federal Reserve Bank of New York, 2005)
This paper reconsiders the cost of business cycles under incomplete markets. Primarily, we focus on the heterogeneity in the cost of business cycles among agents with different skill levels. Unskilled workers are subject to a much larger risk of unemployment during recessions than are skilled workers. Moreover, unskilled workers earn less income, which limits their ability to self-insure. We examine how this heterogeneity in unemployment risk and income translates into heterogeneity in the cost of business cycles. We set up a dynamic general equilibrium model with incomplete markets, in which there is heterogeneity in skills, employment status, asset holding, and the discount factor. We find that the welfare cost of business cycles for unskilled workers is substantially higher than that for skilled workers.
Keywords: E24; E32; E61; 330; cost of business cycles; incomplete markets; skill and unemployment; Konjunktur; Soziale Kosten; Unvollkommener Markt; Ungelernte Arbeitskräfte; Dynamisches Gleichgewicht; Theorie